Hydroboration of vinyl halides with mesitylborane: a direct access to (mesityl)(alkyl)haloboranes. Issue 10 (12th January 2022) - Devillard, Marc; Cordier, Marie; Roisnel, Thierry; Dinoi, Chiara; Del Rosal, Iker; Alcaraz, Gilles
Abstract : The direct access to (mesityl)(alkyl)haloboranes (Mes(Alk)BX) (X = Br, Cl) from mesitylborane dimer and vinyl halides is presented, revealing two accessible pathways, one of which being kinetically favoured. Abstract : The direct access to (mesityl)(alkyl)haloboranes (Mes(Alk)BX) (X = Br, Cl) from mesitylborane dimer and vinyl halides is presented. The involved hydroboration reaction results in the transfer of the halogen atom from the carbon of the starting material to the boron in the final product. The reactivity of the obtained Mes(Alk)BX has been evaluated for the synthesis of the bipyridyl boronium cations and 2-arylpyridine derived boron N^C-chelates. The formation mechanism of Mes(Alk)BX is apprended by DFT-calculations which shows that their formation involves two concomitant pathways derived from the regioslectivity of the hydroboration reaction.